Inflation in Hungary: How Does It Affect the Financial Situation of the Population? - Molnár, László; Hajdú, Noémi (Theory, Methodology, Practice – Review of Business and Management, 2024)
Recent events have affected the economies of nations that began with an extraordinary epidemic that led to the lifting of closures and the emergence of oversupply in the market. The result is price increases, new supply problems and deficit economies, all of which contribute to rising inflation. The conflict and the oil crisis made the situation worse. We wondered whether the recent price increases have made people in Hungary more conscious with their budgets. The current report is based on a nationwide representative survey of almost 25,000 people conducted by NET Media PLC in September 2022. The study focused primarily on the development of living standards and the state of the economy, changes in spending patterns, savings, and family household management. Overall, it can be said that more than 75 percent of Hungarians over 25 are dissatisfied with how their standard of living has changed in the last year and that their financial situation has deteriorated.